Hygrothermal response of fibre reinforced polymer composites - Ng, Wei Jie (Nanyang Technological University, 2022)
For this study, epoxy is employed as a polymer matrix in a fibre reinforced composite. The effect of moisture and heat on the fibre reinforced epoxy composite will be determined by the results of mechanical testing following exposure to hygrothermal conditions. This study focuses on the structural testing on the tensile and flexural properties of the composite before and after exposure to the hygrothermal environment since there is a current lack of understanding and consistency existing in the current literature.